(untitled) (ABUJA JOURNAL OF BUSINESS AND MANAGEMENT, 2025)
This study investigates the relationship between Customer Relationship Management (CRM) practices and organizational performance within selected Deposit Money Banks (DMBs) in the Federal Capital Territory (FCT), Abuja. Utilizing a descriptive survey research design, the study explores the extent to which CRM strategies, including interaction management, relationship development, analytical CRM, and operational CRM, impact key performance indicators such as customer satisfaction, loyalty, commitment, and customer base. A sample of 241 staff members from various departments, including customer service, marketing, management, and operations, was selected using stratified random sampling and simple proportion sampling techniques which is the total population of staff within the selected Deposit Money Banks. Data was collected through structured questionnaires and analyzed using descriptive statistics and simple regression analysis. The results reveal that all CRM dimensions significantly affect organizational performance. Interaction management positively influences customer satisfaction, analytical CRM enhances customer loyalty, relationship development fosters customer commitment, and operational CRM contributes to expanding the customer base. The study recommends that DMBs in Abuja should prioritize improving CRM practices to drive better performance outcomes, particularly in customer satisfaction and loyalty.